Optimization of the Hard Anodizing Process in Acidic Baths on AA6063 Aluminum Alloy Using Response Surface Methodology - Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli; Estupiñan López, Francisco Humberto; Jáquez Muñoz, Jesús Manuel; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2025)
The characteristics of aluminum alloys make them the most extensively used material in the aerospace sector. Aluminum, in a natural way, when interacting with oxygen, forms a protective layer of aluminum oxide, Al2O3, that enhances its properties, for example, resistance to corrosion and fatigue. This work aims to optimize the anodizing process by identifying the optimum values and combination of factors that allow the formation of an alumina layer with a thickness of 12 µm and the maximum Vickers microhardness. The parameters to be evaluated will include time, current density, and sulfuric acid concentration, which were considered variables at two levels: 15 and 20 min, 2.5 and 3.5 A/dm2, and 180 and 350 g/L, respectively. We used the response surface methodology (RSM) with a composite central design (CCD). The results of the optimization MSR reveal that to obtain the optimum Type III hard anodizing on AA6063 aluminum alloy with a target thickness of 11.85 µm and a Vickers microhardness of 297.14, a combination consisting of 15 min, 2.55 A/dm2, and 333.15 g/L of H2SO4 is required.